2017
DOI: 10.1002/ente.201600636
|View full text |Cite
|
Sign up to set email alerts
|

Sustainion Imidazolium‐Functionalized Polymers for Carbon Dioxide Electrolysis

Abstract: CO2 electrolysis is a key step in CO2 conversion into fuels and chemicals as a way of mitigating climate change. We report the synthesis and testing of a series of new anion‐conductive membranes (tradenamed Sustainion™) for use in CO2 electrolysis. These membranes incorporate the functional character of imidazolium‐based ionic liquids as co‐catalysts in CO2 reduction into a solid membrane with a styrene backbone. We find that the addition of an imidazolium group onto the styrene side‐chains increases the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
378
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(395 citation statements)
references
References 47 publications
6
378
0
6
Order By: Relevance
“…Using Co phthalocyanine as catalysts, we have shown that this dogma can be overcome by applying the complex into a flow cell, generating CO with 94 % selectivity at 165 mA cm −2 current density at basic pH (14) . Such performances approach those obtained with Ag‐ and Au‐based catalytic materials . However, the Co complex, like the above mentioned solid nano‐catalysts, operates at quite large overpotential, in the range of 800 mV at comparably current densities.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Using Co phthalocyanine as catalysts, we have shown that this dogma can be overcome by applying the complex into a flow cell, generating CO with 94 % selectivity at 165 mA cm −2 current density at basic pH (14) . Such performances approach those obtained with Ag‐ and Au‐based catalytic materials . However, the Co complex, like the above mentioned solid nano‐catalysts, operates at quite large overpotential, in the range of 800 mV at comparably current densities.…”
Section: Methodsmentioning
confidence: 89%
“…[21,22] Such performances approacht hose obtained with Ag-and Aubased catalytic materials. [23][24][25] However,t he Co complex, like the above mentioned solid nano-catalysts, operatesa tq uite large overpotential,i nt he range of 800 mV at comparably current densities. The selectivity could also be still improved, while the exclusive use of earth abundant elements insteado f expensive metals is mandatory.I nt his context, Fe is an ideal candidate being the most abundant transition metal.…”
mentioning
confidence: 99%
“…Dioxide Materials, MEA‐based : In 2017, Kutz et al. achieved what is, to our knowledge, the longest continuous operation of a CO 2 electroreduction system, using an MEA‐based electrolyzer . The cell was able to run at an applied current density of 200 mA cm −2 for over 1000 h and at 50 mA cm −2 for 6 months (4380 h), at a measured cell potential difference of approximately 3 V (Figure a and b).…”
Section: Recent Durability and Stability Studies Of Cathodes For Co2rrmentioning
confidence: 99%
“…[7,19,20] Apart from the electrodes and catalysts, other important factors that may play a significant role in the electrolytic cell are the ion exchange membrane (IEM) [21,22] and the electrochemical environment. [28,29] Through commercial anionic membranes as FAA-3 (Fumatech) [30] or A-901 (Tokuyama), [31] the rate of product crossover was proportional to the current density. [23] In order to avoid the challenges of using liquid electrolytes, to improve CO 2 solubility and recovery of liquid products, solid polymer electrolyte membranes were introduced in the design of electrochemical flow reactors.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The most studied configuration in flow reactors are membrane reactors, where the membrane role consists just on the physical barrier that separates the anode and the cathode and facilitates the selective transport of ions between them to close the circuit, while simultaneously attenuating the cross-over in the opposite direction and the re-oxidation of the product. [32] Dioxide Materials developed Sustainion@, an AAEM containing imidazolium compounds that improve the performance and selectivity of CO 2 RR to CO. [28,29,33] However, these membrane materials and preparation are usually expensive or highly toxic to health and environment. [7,19,20] The development of alkaline anion-exchange membranes (AAEMs), bipolar membranes and mosaic membranes in opposition to most conventionally employed cation exchange membranes (CEMs), Nafion 117 (DuPont), [24][25][26] is an example of the increasing relevance that the role of the IEM in the electrochemical reaction is gaining in research literature.…”
Section: Introductionmentioning
confidence: 99%